Electronic Properties of Naphthalimide-based Ladder-type Systems - González-Núñez, Raúl; Alonso-Navarro, Matías J.; Harbuzaru, Alexandra; Segura, José L.; Ponce-Ortiz, Rocío (My University, 2023)
The tuneable electronic and structural properties of organic semiconductors together with their flexibility, light weight, high solution processing and low costs in comparison with inorganic semiconductors are some of the key points for the current interest in the development of π-conjugated small molecules and polymers for a variety of applications. In this project, a combined experimental and theoretical study of two ladder-type compounds functionalized with naphthalimides1 (Figure 1) is performed with the aim to explore the impact of the structure on the optical and charge-transport properties. Compound NDI-TP-Ph-TP has an imidazole group as a spacer ring and NIP-TP-Ph-TP has a spacer ring of pyrazine type. The two molecular systems have been implemented in organic field effect transistors2 (OFETs), to assess their potential as active materials in organic electronics. Both compounds show p-type mobility, moreover, NDI-TP-Ph-TP material also displays low n-type mobility, presenting a certain ambipolar character.
Keywords: Semiconductores orgánicos; OFETs; DFT calculations; Organic semiconductors; Ladder-type systems; Organic electronics